Public entrepreneurs and the adoption of broad-based merit aid beyond the Southeastern United States - Ingle, William Kyle; Petroff, Ruth Ann (Education Policy Analysis Archives, 2013)
The concentration of broad-based merit aid adoption in the southeastern United States has been well noted in the literature. However, there are states that have adopted broad-based merit aid programs outside of the Southeast. Guided by multiple theoretical frameworks, including innovation diffusion theory (e.g., Gray, 1973, 1994; Rogers, 2003), Roberts and King’s (1991) typology of public entrepreneurs, and Anderson’s (2003) stages of the policymaking process, this qualitative study sought to answer the following questions. First, in the absence of regional diffusion pressures, what internal determinants are reported as accounting for the diffusion of broad-based merit aid programs outside of the Southeastern US? What types of public entrepreneurs were identified as playing key roles in establishing merit aid in states outside the southeastern US? During which stages of the policymaking process were they active? We found that merit aid was a means of addressing an array of public problems, including low college going rates at in-state public colleges and universities, and weak K-12 accountability. Consistent factors reported as facilitating merit aid creation included a strong, vocal public advocate (governors and a university system president) and a desire to strengthen state economies and diversify workforces. A full range of public entrepreneurs played key roles in developing merit aid in the sampled states. Political and executive entrepreneurs were in the forefront of merit aid efforts, but our data suggest that a cast of supporting public entrepreneurs were integral to the eventual adoption of broad-based merit aid in the sampled states.